Preparation method of stable small-particle-size amino-terminated polysiloxane emulsion and application thereof
Patent Information
- Application Number
- CN202611341278.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-10-20
AI Technical Summary
现有技术尚缺乏针对上述多个过程进行连续协同控制的有效方法
[0035]第一,本发明不是在高黏度氨端聚硅氧烷完全形成后再依靠高强度机械力降低粒径,而是在适宜聚合状态下实施乳化,使聚硅氧烷保持一定分子链长度的同时具有较低的界面变形阻力,从而有利于在较温和机械条件下形成小液滴。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of daily chemical technology, and in particular to a method for preparing a stable small-particle-size ammonia-terminated polysiloxane emulsion and its application. Background Technology
[0002] Amino-terminated polysiloxanes are commonly used silicone conditioning materials in hair care products such as shampoos, conditioners, and hair masks. The polysiloxane backbone has low surface energy, a low glass transition temperature, and high softness, while the amino groups in the molecule have strong polarity, which enhances the affinity of polysiloxanes for damaged hair surfaces. Therefore, it can form a lubricating film on the hair surface, reducing frictional resistance and improving dry combing, wet combing, softness, and antistatic properties of the hair.
[0003] Since ammonia-terminated polysiloxanes typically have high viscosity and are difficult to disperse directly in water, they are usually formulated into oil-in-water emulsions for practical applications.
[0004] The average particle size, particle size distribution, and degree of particle size change during storage of emulsion droplets directly affect the dispersion stability of ammonia-terminated polysiloxanes in shampoo and conditioner compositions and their deposition uniformity on the hair surface.
[0005] Existing ammonia-terminated polysiloxane emulsions are typically prepared using two types of methods.
[0006] The first type involves first preparing a high molecular weight ammonia-terminated polysiloxane base oil, and then breaking down and dispersing the base oil in an aqueous phase using mechanical methods such as high-shear emulsification and high-pressure homogenization. Since the polymerized ammonia-terminated polysiloxane has a high viscosity, its droplet breakup requires a large mechanical energy input; therefore, it is often necessary to increase the amount of emulsifier, increase the homogenization pressure, or extend the shearing time.
[0007] The second type involves the polymerization of cyclic siloxanes in an aqueous or emulsion environment, where the polymerization and emulsification processes partially overlap. However, this process involves simultaneous polymerization rate increases, polymer viscosity growth, emulsifier interfacial migration, and oil-water phase transition, making process control more challenging.
[0008] Further research revealed that for nano- or near-nano-scale ammonia-terminated polysiloxane emulsions, simply reducing the initial particle size is insufficient to guarantee long-term stability.
[0009] As droplet size decreases, the oil-water interface area per unit mass of oil increases significantly. If the emulsifier cannot migrate to the new interface and form a continuous interfacial film in time during rapid droplet formation, even if smaller droplets are temporarily obtained through high-intensity mechanical shearing, the droplets may still re-aggregate during subsequent storage, resulting in an increase in average particle size, a wider particle size distribution, or even oil drift.
[0010] Therefore, the key to small-particle-size emulsions lies not only in "breaking up large droplets", but also in matching the droplet formation rate with the emulsifier interface coverage rate.
[0011] For ammonia-terminated polysiloxanes, the above issues are even more complex.
[0012] Amino functional groups can undergo protonation, and the degree of protonation affects the charge state near the oil-water interface; cationic emulsifiers can also impart positive charge to the droplet surface. If all cationic and nonionic emulsifiers are present in a large aqueous phase before droplet formation, some emulsifiers may preferentially form aqueous aggregates and cannot effectively participate in the formation of the new silicone oil interface.
[0013] Therefore, ensuring that the following factors occur in a suitable time sequence: the degree of polysiloxane chain growth; the pre-distribution of nonionic emulsifiers in the oil phase; the migration of cationic emulsifiers to the nascent interface; the phase inversion from the oil continuous phase to the water continuous phase; and the occurrence of droplet surface charge states are crucial for further reducing the particle size of ammonia-terminated polysiloxane emulsions and improving their long-term stability. Current technologies lack effective methods for the continuous and synergistic control of these multiple processes. Summary of the Invention
[0014] To address the aforementioned technical problems, this invention provides a method for preparing a stable small-particle-size ammonia-terminated polysiloxane emulsion, comprising the following steps:
[0015] (1) Cyclic siloxane D4 and amino functional siloxane monomers are subjected to ring-opening polymerization in the presence of an alkaline catalyst so that the resulting amino-containing polysiloxane reaches the predetermined pre-emulsification polymerization state.
[0016] (2) Adjust the amino-containing polysiloxane obtained in step (1) to 50-60°C, first add dodecyl alcohol polyether-12 for the first pre-interfacial treatment, then add isomeric tridecyl alcohol polyoxyethylene ether-12 for the second pre-interfacial treatment to obtain the pre-interfacialized oil phase.
[0017] (3) Separate the aqueous solution of hexadecyltrimethylammonium chloride into a first cationic aqueous phase and a second cationic aqueous phase;
[0018] (4) Under the conditions of 50-60℃ and stirring, the first cationic aqueous phase is added to the pre-interfacialized oil phase obtained in step (2). When the system enters the phase inversion critical region, the rate of addition of the aqueous phase is controlled so that the system is transformed from the oil continuous phase to the water continuous phase.
[0019] (5) After the phase inversion is complete, add the second cation aqueous phase and the remaining deionized water;
[0020] (6) The pH of the obtained emulsion is adjusted to 7.5-8.0 using an acidic regulator to obtain the stable small particle size ammonia-terminated polysiloxane emulsion;
[0021] The cyclic siloxane D4 comprises 20-30%, and the amino-functionalized siloxane monomer comprises 0.5-1.5%.
[0022] The dodecyl alcohol polyether-12 is 3-5%, and the isomeric tridecyl alcohol polyoxyethylene ether-12 is 3-5%;
[0023] The mass ratio of dodecyl alcohol polyether-12 to isotridecyl alcohol polyoxyethylene ether-12 is 0.75 to 1.30:1.
[0024] The ring-opening polymerization temperature in step (1) is 100-110℃.
[0025] The first cationic aqueous phase contains 30-70% of the total amount of hexadecyltrimethylammonium chloride, and the second cationic aqueous phase contains the remainder of hexadecyltrimethylammonium chloride.
[0026] The mass ratio of hexadecyltrimethylammonium chloride in the first cationic aqueous phase and the second cationic aqueous phase is 40–60:60–40.
[0027] In step (4), the rate of water phase addition in the reverse inversion critical region is lower than the rate of water phase addition after the reverse inversion is completed.
[0028] In step (4), the stirring speed is 800-1000 rpm.
[0029] The zeta potential of the emulsion obtained in step (6) is +20 to +35 mV.
[0030] A stable small-particle-size ammonia-terminated polysiloxane emulsion, characterized in that it is prepared by the method described above, wherein the Z-average particle size of the emulsion is 20-50 nm and the PDI is not greater than 0.20.
[0031] The Z-average particle size is 25–40 nm, and the PDI is not greater than 0.15.
[0032] A hair care composition, characterized in that it comprises the aforementioned ammonia-terminated polysiloxane emulsion, as well as anionic surfactants and / or amphoteric surfactants.
[0033] The application of the aforementioned ammonia-terminated polysiloxane emulsion in shampoos, conditioners, hair masks, or scalp care products.
[0034] Compared with the prior art, the present invention has at least the following beneficial effects.
[0035] First, this invention does not rely on high-intensity mechanical force to reduce the particle size after the high-viscosity ammonia-terminated polysiloxane has been fully formed. Instead, it performs emulsification under suitable polymerization conditions, so that the polysiloxane maintains a certain molecular chain length while having low interfacial deformation resistance, which is conducive to the formation of small droplets under milder mechanical conditions.
[0036] Secondly, the present invention adopts a pre-interface formation method in which dodecyl alcohol polyether-12 is added first and isomeric tridecyl alcohol polyoxyethylene ether-12 is added later, so that the two nonionic emulsifiers with different structures are pre-distributed in the amino-containing polysiloxane oil phase before a large amount of aqueous phase enters, thereby achieving a high effective emulsifier coverage during the formation of the new interface.
[0037] Third, the present invention adds hexadecyltrimethylammonium chloride in stages, so that the first part participates in phase inversion and the formation of new interface, and the second part further supplements the interface electrical stability after phase inversion, thereby avoiding the decrease in effective interface utilization caused by adding all the cationic emulsifier to the aqueous phase at once.
[0038] Fourth, this invention independently controls the phase inversion critical region. By reducing or maintaining a low aqueous phase addition rate, the formation rate of the new oil-water interface is adapted to the migration and alignment rate of the emulsifier to the interface, thereby reducing the immediate re-aggregation of droplets after formation.
[0039] Fifth, this invention controls the final pH to ensure that the protonated state of the amino-containing polysiloxane, the positive interfacial charge formed by the cationic emulsifier, and the steric hindrance generated by the dual nonionic emulsifier are in a more suitable coordination state, rather than simply pursuing a larger Zeta potential.
[0040] Sixth, this invention can obtain ammonia-terminated polysiloxane emulsions with small particle size and narrow particle size distribution. In a specific embodiment, the obtained emulsion has a Z-average particle size of 31.7 nm, a PDI of 0.125, and a Zeta potential of +25.34 mV.
[0041] Seventh, the resulting emulsion has good long-term storage properties and is suitable for addition to shampoo compositions containing anionic surfactants, which can improve the wet combability, dry combability, wet rinse smoothness, dry smoothness, and antistatic properties of hair. Detailed Implementation
[0042] The present invention will be further explained below with reference to specific embodiments.
[0043] This invention addresses the problems of existing ammonia-terminated polysiloxane emulsions in the preparation and application of hair care products, such as large emulsion particle size, wide particle size distribution, the need for high shear strength or high homogenization pressure to obtain smaller particle size, easy droplet aggregation and particle size rebound during long-term storage, and easy turbidity, flocculation, oil floating or viscosity decrease after compounding in shampoo compositions containing anionic surfactants. It provides a stable small particle size ammonia-terminated polysiloxane emulsion and its preparation method.
[0044] This invention does not simply reduce droplet size by increasing the amount of emulsifier or improving mechanical shear strength. Instead, it continuously controls the degree of polymerization of cyclic siloxanes, the contact sequence of the two nonionic emulsifiers with amino-containing polysiloxanes, the timing of the addition of cationic emulsifiers, the oil-to-water phase transition process, and the final pH of the emulsion. This allows the amino-containing polysiloxanes to enter the emulsification process with suitable molecular chain lengths while still maintaining good interfacial deformability. It also allows emulsifiers with different structures to enter the newly formed oil-water interface in a predetermined order, thereby reducing the initial size of the newly formed droplets and inhibiting the re-agglomeration of the resulting droplets during storage.
[0045] Furthermore, this invention adds dodecyl alcohol polyether-12 and isomeric tridecyl alcohol polyoxyethylene ether-12 to an amino-containing polysiloxane in a specific order, so that the former is preferentially distributed in the polysiloxane oil phase, and then the branched hydrophobic structure of the latter is used to supplement the interfacial steric hindrance; at the same time, hexadecyltrimethylammonium chloride is introduced in stages before and after phase inversion, so that it participates in the formation of new interface and the stabilization of interface after phase inversion, respectively, thereby matching the interfacial migration process of the emulsifier with the droplet generation process.
[0046] Through the above treatment, the present invention can prepare an amino-terminated polysiloxane emulsion with a Z-average particle size preferably of 20-50 nm and a PDI preferably not greater than 0.20 under relatively mild stirring and homogenization conditions, and the resulting emulsion has good high-temperature, low-temperature and shampoo matrix compounding stability.
[0047] To achieve the above objectives, the present invention adopts the following technical solution.
[0048] (I) Stabilized small-particle-size ammonia-terminated polysiloxane emulsion
[0049] This invention provides a stable, small-particle-size, amino-terminated polysiloxane emulsion, comprising the following raw materials based on 100% of the total mass of the final emulsion:
[0050] Cyclic siloxane D4 20-30%; amino-functionalized siloxane monomer 0.5-1.5%; hexadecyltrimethylammonium chloride aqueous solution 20-30%; dodecyl alcohol polyether-12 3-5%; isomeric tridecyl alcohol polyoxyethylene ether-12 3-5%; alkaline catalyst 0.3-0.5%; acid regulator 0.5-1.0%; deionized water 35-45%.
[0051] Preferably, the cyclic siloxane D4 is 20-25%, more preferably 20-22%, and in one specific embodiment, it is 20%.
[0052] Preferably, the amino-functionalized siloxane monomer is 0.8-1.2%, more preferably 0.9-1.1%, and in one specific embodiment, it is 1.0%.
[0053] Preferably, the dodecyl alcohol polyether-12 is 4.0-5.0%, more preferably 4.5-5.0%, and in one specific embodiment, it is 5.0%.
[0054] Preferably, the isomeric tridecyl alcohol polyoxyethylene ether-12 is 4.0-5.0%, more preferably 4.5-5.0%, and in one specific embodiment, it is 5.0%.
[0055] Preferably, the mass ratio of dodecyl alcohol polyether-12 to isotridecyl alcohol polyoxyethylene ether-12 is 0.75 to 1.30:1.
[0056] Further preferred is 0.85–1.20:1. Even more preferred is 0.90–1.10:1. Particularly preferred is 0.95–1.05:1.
[0057] In one specific embodiment, the mass ratio of dodecyl alcohol polyether-12 to isotridecyl alcohol polyoxyethylene ether-12 is 1:1.
[0058] This invention has found that when the mass ratio of the two is significantly lower than the above range, the proportion of branched nonionic emulsifier in the interface film is relatively high. Although it can form a certain steric hindrance, it is insufficient for the initial wetting of the polysiloxane oil phase and continuous interface coverage, which can easily cause some droplets formed in the early stage of emulsification to be larger in size.
[0059] When the mass ratio of the two is significantly higher than the above range, although the interface coverage can be formed relatively quickly, the interface space barrier provided by the branched chain is insufficient, and the droplets are prone to collision and aggregation after the reverse rotation.
[0060] Therefore, controlling the two within the above-mentioned ratio range, especially close to 1:1, can achieve a better balance between interface forming ability and anti-agglomeration ability after droplet formation.
[0061] (II) Preparation method
[0062] This invention also provides a method for preparing the above-mentioned stable small-particle-size ammonia-terminated polysiloxane emulsion, comprising the following steps:
[0063] S1. Cyclic siloxane D4 and amino-functionalized siloxane monomers are pretreated and then subjected to ring-opening polymerization in the presence of an alkaline catalyst to obtain amino-containing polysiloxane material in the pre-emulsification polymerization state.
[0064] S2. Cool the amino-containing polysiloxane material obtained in step S1 to 50-60°C, first add dodecyl alcohol polyether-12 for the first pre-interfacial treatment, then add isomeric tridecyl alcohol polyoxyethylene ether-12 for the second pre-interfacial treatment to obtain the pre-interfacialized oil phase.
[0065] S3. Divide the hexadecyltrimethylammonium chloride aqueous solution into a first cationic emulsion and a second cationic emulsion;
[0066] S4. Under stirring conditions of 50-60℃ and 800-1000 rpm, the first cationic emulsion is added to the pre-interfacialized oil phase obtained in step S2. After the system enters the phase inversion critical region, the addition rate of the aqueous phase is controlled so that the system gradually changes from an oil continuous phase to a water continuous phase.
[0067] S5. After the phase inversion is completed, add the second cationic emulsion and the remaining deionized water;
[0068] S6. The pH of the resulting emulsion is adjusted to 7.5-8.0 using an acidic regulator, and the mixture is stirred evenly to obtain a stable small-particle-size ammonia-terminated polysiloxane emulsion.
[0069] If necessary, step S7 is also included: low-intensity homogenization of the emulsion obtained in step S6 to further reduce the proportion of a small number of large-diameter droplets and narrow the emulsion particle size distribution.
[0070] III. Control during the aggregation phase
[0071] In step S1, before the polymerization reaction, it is preferable to dehydrate the cyclic siloxane D4 and the amino-functionalized siloxane monomer so that the moisture content of the raw materials participating in the polymerization is not higher than 0.05%.
[0072] Preferably, the cyclic siloxane D4 and the amino-functionalized siloxane monomer are mixed and then first heated to 80–90°C. More preferably, the temperature is 83–88°C. In one specific embodiment, the temperature is 85°C.
[0073] An alkaline catalyst was then added, and the temperature was raised to 100–110°C to carry out ring-opening polymerization.
[0074] The preferred polymerization temperature is 102–108°C. More preferably, it is 104–106°C. In one specific embodiment, it is 105°C.
[0075] The polymerization reaction does not necessarily have to proceed to the formation of the highest viscosity ammonia-terminated polysiloxane base oil. Instead, it proceeds to the subsequent emulsification step when the amino-containing polysiloxane has formed a certain chain length and the oil phase still has suitable fluidity and interfacial deformation ability.
[0076] This invention refers to the above-mentioned state as the "pre-emulsification polymerization state". The pre-emulsification polymerization state can be determined based on reaction time, material viscosity, refractive index, or a combination of the above indicators.
[0077] For example, under the same reaction temperature and raw material ratio, materials with different degrees of polymerization can be obtained by different reaction times, and the appropriate process range can be determined by the particle size and PDI obtained by subsequent emulsification.
[0078] The reason for adopting the above settings is that the degree of polymerization of amino-containing polysiloxanes is not a simple positive correlation with subsequent emulsification performance. If the degree of polymerization is too low, the proportion of oligomers in the system will be high, and the composition of the oil phase may change further during subsequent storage, thereby affecting the interfacial stability.
[0079] If the degree of polymerization is too high, the viscosity of amino-containing polysiloxanes increases, and when forming droplets, greater viscous resistance and interfacial deformation resistance need to be overcome, requiring higher shear strength to obtain smaller particle sizes.
[0080] Therefore, the present invention preferably selects a suitable pre-emulsification polymerization state between the two, so as to balance the formation of polysiloxane segments and the subsequent interfacial dispersion ability.
[0081] IV. Sequential pre-interfacialization with dual nonionic emulsifiers
[0082] In step S2, the amino-containing polysiloxane material obtained in step S1 is cooled to 50–60°C. Preferably, it is 52–58°C. More preferably, it is 54–56°C. In one specific embodiment, it is 55°C.
[0083] First, add dodecyl alcohol polyether-12; after addition, preferably stir at 300-700 rpm for 10-30 min; more preferably stir at 400-600 rpm for 15-25 min; in one specific embodiment, stir at 500 rpm for 20 min.
[0084] After completing the first pre-interfacial treatment, add isomeric tridecyl alcohol polyoxyethylene ether-12; preferably continue stirring at 300-700 rpm for 10-30 min; more preferably at 500 rpm for 20 min; the present invention adopts the above-mentioned order of addition, instead of adding the two nonionic emulsifiers at once after premixing them.
[0085] Among them, dodecyl alcohol polyether-12 has relatively regular long-chain hydrophobic groups and polyoxyethylene hydrophilic chains. Before a large amount of aqueous phase is added, it first contacts the amino-containing polysiloxane, which is conducive to the full distribution of its hydrophobic part in the polysiloxane oil phase and reduces the free energy of subsequent oil-water interface formation. Then, isomeric tridecyl alcohol polyoxyethylene ether-12 is added. The hydrophobic group of this emulsifier has a certain branched structure. After coexisting with the aforementioned dodecyl alcohol polyether-12 in the oil phase, it can migrate together to the new interface when the subsequent aqueous phase enters. It also reduces the probability of adjacent droplets further approaching and coalescing by occupying more space.
[0086] Therefore, the two pretreatments mentioned above do not have the same effect.
[0087] The first stage is mainly beneficial to improve the coverage continuity in the early stage of interface formation; the second stage is mainly beneficial to improve the spatial stability of the interface after formation. Adopting the above order can enable the two types of effects to play their roles in the opposite inversion process and reduce the possibility of non-selective aggregation after all emulsifiers are added at the same time.
[0088] V. Staged addition of cationic emulsifiers
[0089] In step S3, it is preferable to divide the hexadecyltrimethylammonium chloride aqueous solution into a first cationic emulsion and a second cationic emulsion.
[0090] The first cationic emulsion contains 30-70% hexadecyltrimethylammonium chloride in its total addition; the second cationic emulsion contains the remainder hexadecyltrimethylammonium chloride; preferably, the mass distribution ratio of hexadecyltrimethylammonium chloride in the two parts is 40-60:60-40; more preferably 45-55:55-45; in one specific embodiment, it is 50:50.
[0091] For example, when using 60.0 g of a 30% hexadecyltrimethylammonium chloride aqueous solution, it can be divided into 30.0 g of a first cationic emulsion and 30.0 g of a second cationic emulsion.
[0092] In another specific embodiment, the ratio may be 27.0 g:33.0 g; in yet another specific embodiment, the ratio may be 33.0 g:27.0 g.
[0093] The first cationic emulsion and the second cationic emulsion are preheated to 50-60°C, preferably around 55°C. The first cationic emulsion is mainly used for the formation and stabilization of the interface before and during the phase inversion. The second cationic emulsion is mainly used to further replenish and stabilize the already formed droplet interface after the phase inversion.
[0094] This invention has found that if all hexadecyltrimethylammonium chloride is added at once before the phase inversion, although the resulting droplets can also obtain a high positive charge, some of the cationic emulsifier may exist in the continuous aqueous phase in advance and cannot fully participate in the formation of a large number of newly formed oil-water interfaces in the phase inversion critical region.
[0095] Therefore, the stability of an emulsion does not depend solely on the final zeta potential, but also on the time it takes for the cationic emulsifier to reach the oil-water interface.
[0096] VI. Control of the reverse inversion process
[0097] In step S4, the pre-interfacialized oil phase is maintained at 50-60°C; preferably 54-56°C; in one specific embodiment, it is 55°C; the stirring speed is 800-1000 rpm; preferably 850-950 rpm; in one specific embodiment, it is 900 rpm; the first cationic emulsion is added to the pre-interfacialized oil phase in a continuous or segmented manner.
[0098] In the initial stage of addition, the system is still in the oil continuous phase state; as the proportion of water phase gradually increases, the viscosity of the system gradually increases and approaches the phase inversion critical region; the phase inversion critical region can be judged by at least one of the following: a significant increase in system viscosity, a change in stirring resistance, a change in appearance from a relatively transparent or semi-transparent state to a milky white state, and a change in the properties of the continuous phase.
[0099] Before entering the phase inversion critical region, it is preferable to use a lower first aqueous phase addition rate; after entering the phase inversion critical region, maintain the first addition rate or further reduce the addition rate; after the phase inversion is completed, increase the subsequent aqueous phase addition rate.
[0100] The reason for adopting this setting is that the reverse inflection critical region is one of the stages in which the newly formed oil-water interface increases the fastest per unit time.
[0101] If the aqueous phase is added too quickly at this stage, the rate at which the area of the newly formed interface increases may exceed the rate at which the emulsifier migrates from the oil and aqueous phases to the interface, resulting in insufficient emulsifier coverage at the local interface, and the newly formed droplets will then re-aggregate.
[0102] By reducing the rate at which the aqueous phase is added to the critical phase inversion region, the rate at which the oil-water interface is formed can be better matched with the migration rates of dodecyl alcohol polyether-12, isotridecyl alcohol polyoxyethylene ether-12, and hexadecyltrimethylammonium chloride to the interface.
[0103] This reduces the proportion of large droplets in the early stages of emulsification; this process is one of the important steps in obtaining a small-particle-size and low-PDI emulsion in this invention.
[0104] VII. The interface after inversion is stabilized.
[0105] After the phase reversal from the oil continuous phase to the water continuous phase is completed, a second cationic emulsion is added. The addition rate of the second cationic emulsion can be higher than the addition rate of the first cationic emulsion in the phase reversal critical region. After adding the second cationic emulsion, the remaining deionized water is added to adjust the emulsion to a predetermined solid content. Stirring is preferably continued for 20 to 40 minutes, more preferably for 25 to 35 minutes, and in one specific embodiment for 30 minutes.
[0106] At this stage, droplets are basically formed, and the second part, hexadecyltrimethylammonium chloride, is further distributed in the already formed oil-water interface and continuous aqueous phase, further enhancing the electrostatic repulsion between droplets based on the steric stabilization provided by the dual nonionic emulsifiers.
[0107] The resulting droplet interface simultaneously possesses: nonionic steric stabilization provided by dodecyl alcohol polyether-12 and isomeric tridecyl alcohol polyoxyethylene ether-12; and electrostatic repulsion provided by the combined interfacial electrical properties of hexadecyltrimethylammonium chloride and amino-containing polysiloxane.
[0108] pH adjustment
[0109] In step S6, the pH of the obtained emulsion is adjusted using an acidic regulator, preferably glacial acetic acid, and the final pH of the emulsion is 7.5-8.0; preferably 7.6-7.9; more preferably 7.7-7.9; 7.8 in one specific embodiment; 7.7 in another specific embodiment; and 7.9 in yet another specific embodiment.
[0110] Controlling the pH range not only makes the product suitable for daily chemical washing and care formulations, but also affects the degree of protonation of amino functional groups. When the pH is too high, the degree of protonation of nitrogen-containing groups in amino-containing polysiloxanes decreases, the surface positive charge of droplets decreases, and the electrostatic repulsion between droplets weakens. When the pH is too low, the degree of protonation of amino-containing groups increases significantly. Although the Zeta potential may be further increased, the interfacial hydrophilicity and the arrangement state between different emulsifiers change, which may also be detrimental to the long-term stability of the emulsion.
[0111] Therefore, the present invention does not simply pursue a large absolute value of Zeta potential, but rather aims to achieve a state of mutual matching between the electrical stability and steric hindrance stability of the emulsion; preferably, the resulting emulsion has a Zeta potential of +20 to +35 mV; more preferably, +23 to +30 mV; even more preferably, +24 to +28 mV; and in one specific embodiment, it is +25.34 mV.
[0112] Low-intensity particle size shaping
[0113] In the preparation process of this invention, low-intensity homogenization can be selectively implemented according to the particle size distribution of the emulsion. The main purpose of the homogenization is not to force a large number of micron-sized droplets into nano-sized droplets by mechanical energy, but to further shape the small number of larger droplets remaining during the phase inversion process. Therefore, compared with the conventional method of first preparing high-viscosity silicone oil and then using high-pressure homogenization to obtain small particle size, this invention can reduce the contribution of mechanical energy to the emulsification process. In some embodiments, when the phase inversion process has already made the obtained emulsion reach the target particle size and PDI, subsequent high-intensity homogenization can be omitted.
[0114] Parameters of the obtained emulsion
[0115] The stable, small-particle-size ammonia-terminated polysiloxane emulsion prepared by the above method preferably has a Z-average particle size of 20–50 nm; more preferably 25–45 nm; even more preferably 28–40 nm; particularly preferably 30–38 nm; and in one specific embodiment, 31.7 nm. The resulting emulsion preferably has a PDI of no more than 0.20; more preferably no more than 0.18; even more preferably no more than 0.15; and in one specific embodiment, 0.125.
[0116] The zeta potential of the emulsion is preferably +20 to +35 mV; in one specific embodiment it is +25.34 mV; the resulting emulsion preferably shows no obvious oil floating, layering and precipitation after being stored at 45°C for 90 days; the resulting emulsion preferably shows no obvious oil floating, layering and precipitation after being stored at 0°C for 90 days.
[0117] Hair shampoo and conditioner combination
[0118] The present invention also provides a hair washing and care composition comprising the above-mentioned stable small particle size amino-terminated polysiloxane emulsion; the hair washing and care composition may be a shampoo, conditioner, hair mask, scalp care solution, 2-in-1 washing and care product or other daily chemical composition applicable to hair.
[0119] Preferably, the amount of the ammonia-terminated polysiloxane emulsion added to the final hair shampoo and conditioner composition is 0.1 to 5.0 wt%; more preferably 0.3 to 3.0 wt%; even more preferably 0.5 to 2.0 wt%; and in one specific embodiment, it is 1.0 wt%.
[0120] When the hair care composition is a shampoo, the shampoo may further include one or more of anionic surfactants, amphoteric surfactants, nonionic surfactants, cationic conditioning polymers, thickeners, preservatives, chelating agents, pH adjusters, and fragrances.
[0121] The anionic surfactant may be selected from at least one of sodium lauryl ether sulfate, sodium lauroyl sarcosinate, cocoyl glutamate, and methyl cocoyl taurate.
[0122] The amphoteric surfactant may be cocamidopropyl betaine.
[0123] In one specific embodiment, the hair care composition comprises 16 wt% sodium laureth sulfate, 5 wt% sodium lauroyl sarcosinate, 10 wt% cocamidopropyl betaine, and 1 wt% of the amino-terminated polysiloxane emulsion of the present invention.
[0124] Because the emulsion obtained by this invention has smaller and more uniform droplets and a relatively stable interface structure, it can still maintain a good dispersion state even after entering a shampoo composition containing a high proportion of anionic surfactants, reducing the possibility of local strong interaction between ammonia-terminated polysiloxanes and anionic surfactants, which could cause emulsion flocculation and oil separation.
[0125] Selection and dosage of cyclic siloxane D4
[0126] This invention uses cyclic siloxane D4 as the main raw material for forming the polysiloxane backbone.
[0127] The amount added, based on the total mass of the final emulsion, can be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, or 30%. Preferably, it is 20-25%; more preferably, 20-22%; and 20% is used in the preferred values. In an emulsion with a total mass of 200 g, the specific amount of cyclic siloxane D4 added is 40.0 g.
[0128] When the D4 dosage is too low, the effective polysiloxane content in the resulting emulsion is low, which is not conducive to increasing the effective concentration of the emulsion when used as a washing and conditioning agent. When the D4 dosage is too high, the ratio of the continuous aqueous phase to the oil phase of the emulsifier increases, and the oil-water interface that needs to be covered by a unit of emulsifier under the same total amount of emulsifier increases, making it more difficult to stabilize small-diameter droplets; therefore, this invention controls the D4 content to 20-30 wt%, especially 20-25 wt%.
[0129] Aminofunctional siloxane monomers
[0130] The amount of aminofunctional siloxane monomer added is 0.5% to 1.5% based on the final emulsion mass; for example, it can be 0.5%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4% or 1.5%; preferably 0.8% to 1.2%; in a preferred value, it is 1.0%; when the total emulsion mass is 200 g, the amount added is 2.0 g.
[0131] When amino functional monomers participate in the formation of polysiloxanes, the resulting polysiloxanes possess nitrogen-containing functional groups that can interact strongly with damaged hair areas; if the proportion of amino functional monomers is too low, the adsorption enhancement effect on the hair surface is insufficient.
[0132] If its proportion is too high, the polarity and interfacial charge of the polymer will increase, and it may also have a significant impact on the polymerization reaction and emulsification behavior. Therefore, it is best to control it to 0.5 to 1.5 wt%, especially about 1.0 wt%, which can balance the smoothing and lubricating properties of the polysiloxane chain and the hair affinity of the amino functional groups.
[0133] Preferred ratio of dual nonionic emulsifiers
[0134] The amount of dodecyl alcohol polyether-12 added can be 3.0%, 3.5%, 4.0%, 4.5% or 5.0%; the amount of isotridecyl alcohol polyoxyethylene ether-12 added can be 3.0%, 3.5%, 4.0%, 4.5% or 5.0%; preferably 4 to 5% for both; particularly preferably 5% for both; under the condition of a total mass of 200 g, 10.0 g of dodecyl alcohol polyether-12 and 10.0 g of isotridecyl alcohol polyoxyethylene ether-12 are added respectively.
[0135] The mass ratio of the two can be: 0.75:1; 0.80:1; 0.90:1; 0.95:1; 1.00:1; 1.05:1; 1.10:1; 1.20:1; 1.30:1, preferably 0.90 to 1.10:1, and most preferably 1:1. Using a 1:1 ratio ensures that dodecyl alcohol polyether-12 sufficiently reduces the interfacial resistance when amino-containing polysiloxanes form an oil-water interface, and also utilizes the branched structure of isomeric tridecyl alcohol polyoxyethylene ether-12 to improve the spatial barrier capability of the interfacial layer.
[0136] First pre-interface processing
[0137] After the amino-containing polysiloxane is cooled to 55°C, dodecyl alcohol polyether-12 is added first. The preferred stirring speed is 500 rpm; the preferred processing time is 20 min; the ranges that can be used include 300–700 rpm and 10–30 min.
[0138] For example, the following treatments can be used: 400 rpm for 25 min; 500 rpm for 20 min; 600 rpm for 15 min. 500 rpm for 20 min is preferred. The above treatments allow dodecyl alcohol polyether-12 to fully enter the amino-containing polysiloxane phase.
[0139] Second pre-interface processing
[0140] After the first pre-interfacialization is completed, isomeric tridecyl alcohol polyoxyethylene ether-12 is added at 55°C; preferably, stirring is continued at 500 rpm for 20 min; the stirring speed can be selected as 300-700 rpm, and the processing time is 10-30 min; for example, it can be: 400 rpm, 25 min; 500 rpm, 20 min; 600 rpm, 15 min; through this step, both nonionic emulsifiers are fully distributed in the amino-containing polysiloxane before being added to the aqueous phase; wherein, the two nonionic emulsifiers are preferably not mixed in advance, but added sequentially.
[0141] Partition of hexadecyltrimethylammonium chloride
[0142] Taking a total emulsion mass of 200 g as an example, add 60.0 g of a 30% (w / w) hexadecyltrimethylammonium chloride aqueous solution; preferably, divide it into a first part of 30.0 g and a second part of 30.0 g; or alternatively, divide it into: 24.0 g and 36.0 g; 27.0 g and 33.0 g; 30.0 g and 30.0 g; 33.0 g and 27.0 g; 36.0 g and 24.0 g, i.e., according to a ratio of 40:60 to 60:40; preferably 45:55 to 55:45, and most preferably 50:50.
[0143] If the proportion added before phase inversion is too low, there will be insufficient cationic emulsifier available in the critical phase inversion region, and the formation rate of the new interface electrical stability will be slow. If the proportion before phase inversion is too high, there will be insufficient cationic emulsifier available to supplement the interface stability after phase inversion. At the same time, excessive cationic emulsifier may be distributed in the aqueous phase earlier, reducing the interface utilization efficiency. Therefore, it is preferable to use a near-equal proportion.
[0144] Preferred polymerization temperature
[0145] The polymerization temperature is 100–110°C; for example, it can be 100°C, 102°C, 104°C, 105°C, 106°C, 108°C, or 110°C; preferably 103–108°C; more preferably 104–106°C; the optimal value is 105°C. At this temperature, cyclic siloxanes can undergo effective ring-opening polymerization, while the polymerization rate is easily controlled, allowing the reaction system to accurately enter the subsequent emulsification step before reaching a high viscosity state.
[0146] Preferred emulsification temperature
[0147] The emulsification process temperature is 50-60℃; for example, it can be 50℃, 52℃, 54℃, 55℃, 56℃, 58℃ or 60℃; preferably 53-57℃; most preferably 55℃.
[0148] At excessively low temperatures, the viscosity of amino-containing polysiloxanes increases, and the diffusion and interfacial migration rates of nonionic emulsifiers in the oil phase decrease. At excessively high temperatures, although the viscosity of the oil phase decreases, the hydrophilic-lipophilic balance of the emulsifier and its phase inversion behavior also change, making it difficult to stably control the critical phase inversion region; therefore, around 55°C is the preferred operating temperature.
[0149] Preferred emulsification stirring speed
[0150] The stirring speed during reverse rotation is 800–1000 rpm. For example, it can be 800 rpm, 850 rpm, 900 rpm, 950 rpm, or 1000 rpm; preferably 850–950 rpm; the optimal value is 900 rpm.
[0151] At this stirring intensity, mechanical action is sufficient to achieve macroscopic mixing of the oil and water phases. At the same time, this invention still mainly relies on interface formation control rather than on strong mechanical breakage to form small droplets.
[0152] Preferred pH
[0153] The final emulsion pH is 7.5–8.0; specifically, it can be 7.5, 7.6, 7.7, 7.8, 7.9, or 8.0; preferably 7.7–7.9; the optimal value is 7.8. At the above pH, the nitrogen-containing groups of the amino-containing polysiloxane are in a suitable protonated state, and the resulting emulsion maintains a suitable positive Zeta potential. In the preferred embodiment, the Zeta potential is +25.34 mV.
[0154] Optimal point value technical solution
[0155] In one preferred embodiment, the preparation of 200.0 g of a stable, small-particle-size ammonia-terminated polysiloxane emulsion is as follows:
[0156] Cyclic siloxane D4: 40.0 g; amino-functionalized siloxane monomer: 2.0 g; 30 wt% hexadecyltrimethylammonium chloride aqueous solution: 60.0 g; dodecyl alcohol polyether-12: 10.0 g; isomeric tridecyl alcohol polyoxyethylene ether-12: 10.0 g; potassium hydroxide: 1.0 g; glacial acetic acid: 2.0 g; deionized water: 75.0 g.
[0157] First, the cyclic siloxane D4 and amino-functionalized siloxane monomers are dehydrated to reduce the water content of the raw materials to less than 0.05%. The two raw materials are then added to a reactor and heated to 85°C under stirring at 300 rpm. After adding an alkaline catalyst, the temperature is further increased to 105°C to carry out ring-opening polymerization.
[0158] When the amino-containing polysiloxane reaches the pre-emulsification polymerization state, further polymerization is terminated and the temperature is lowered to 55°C. First, 10.0 g of dodecyl alcohol polyether-12 is added and stirred at 500 rpm for 20 min. Then, 10.0 g of isomeric tridecyl alcohol polyoxyethylene ether-12 is added and stirred at 500 rpm for another 20 min.
[0159] A 60.0 g solution of 30% hexadecyltrimethylammonium chloride was divided into 30.0 g of a first cationic emulsion and 30.0 g of a second cationic emulsion. The first cationic emulsion was preheated to 55°C, and the pre-interfacialized oil phase was maintained at 55°C. The stirring speed was increased to 900 rpm, and the first cationic emulsion was slowly added. As the aqueous phase was added, the viscosity of the system gradually increased. When approaching the phase inversion critical region, a low aqueous phase addition rate was maintained to allow the new interface to gradually form.
[0160] After confirming that the system has changed from an oil continuous phase to an aqueous continuous phase, 30.0 g of the second cationic emulsion and the remaining deionized water were added; stirring was continued at 900 rpm for 30 min, and the pH of the emulsion was adjusted to 7.8±0.1 using glacial acetic acid. Then, stirring was continued at 500 rpm for 20 min, and the mixture was cooled to room temperature.
[0161] The resulting emulsion had an average Z-particle size of 31.7 nm, a PDI of 0.125, and a Zeta potential of +25.34 mV.
[0162] The emulsion showed no obvious oil floating, stratification, or sedimentation after being placed at 45°C for 90 days; similarly, it showed no obvious oil floating, stratification, or sedimentation after being placed at 0°C for 90 days.
[0163] This specific embodiment shows that by coordinating the degree of polymerization of amino-containing polysiloxanes, the pre-distribution of two nonionic emulsifiers, the entry time of cationic emulsifiers, the generation rate of phase inversion interfaces, and the final charge state, it is possible to obtain amino-terminated polysiloxane emulsions with smaller particle sizes and narrower particle size distributions without solely relying on high-intensity mechanical homogenization.
[0164] I. Implementation Examples
[0165] Example 1
[0166] This embodiment provides a stable small-particle-size ammonia-terminated polysiloxane emulsion.
[0167] Based on a total emulsion mass of 200.0 g, the raw materials include: 40.0 g of cyclic siloxane D4, 2.0 g of amino-functionalized siloxane monomer, 60.0 g of 30% hexadecyltrimethylammonium chloride aqueous solution, 10.0 g of dodecyl alcohol polyether-12, 10.0 g of isomeric tridecyl alcohol polyoxyethylene ether-12, 1.0 g of potassium hydroxide, 2.0 g of glacial acetic acid, and 75.0 g of deionized water.
[0168] The specific preparation method is as follows.
[0169] (1) The cyclic siloxane D4 and amino functional siloxane monomers are pre-dehydrated to reduce the moisture content of the raw materials to less than 0.05%.
[0170] (2) Add 40.0 g of cyclic siloxane D4 and 2.0 g of amino functional siloxane monomer to a dry reaction vessel equipped with a stirrer, thermometer and reflux condenser. Stir at 300 rpm and heat to 85°C. Add potassium hydroxide and continue heating to 105°C to carry out ring-opening polymerization.
[0171] The polymerization process is controlled to ensure the reactants reach a predetermined pre-emulsification polymerization state. The polymerization state is determined by changes in material viscosity and refractive index during the reaction. Once the predetermined state is reached, further polymerization is stopped, and catalyst termination treatment is performed.
[0172] The resulting amino-containing polysiloxane material was cooled to 55°C.
[0173] (3) Keep at 55°C. First, add 10.0 g of dodecyl alcohol polyether-12 to the amino-containing polysiloxane material and stir at 500 rpm for 20 min to fully disperse it in the oil phase.
[0174] Then, 10.0 g of isotridecyl alcohol polyoxyethylene ether-12 was added, and the mixture was stirred at 500 rpm for 20 min to obtain a pre-interfacialized oil phase. The mass ratio of dodecyl alcohol polyether-12 to isotridecyl alcohol polyoxyethylene ether-12 was 1:1.
[0175] (4) Divide 60.0 g of a 30% hexadecyltrimethylammonium chloride aqueous solution into two cationic emulsions by mass: the first cationic emulsion and the second cationic emulsion. Add a portion of deionized water to each and preheat to 55°C.
[0176] (5) Maintain the pre-interfacialized oil phase obtained in step (3) at 55°C and increase the stirring speed to 900 rpm.
[0177] The first cationic emulsion was slowly added to the oil phase. The aqueous phase was added at a low rate before the phase inversion. After observing a significant increase in the viscosity of the system and its entry into the critical phase inversion state, the aqueous phase was added at a low rate to allow the system to gradually complete the phase transition from the oil continuous phase to the water continuous phase.
[0178] (6) After confirming that the system has completed the phase inversion, add the second cationic emulsion and the remaining deionized water.
[0179] Continue stirring for 30 minutes.
[0180] (7) Add glacial acetic acid to adjust the pH of the emulsion to 7.8±0.1.
[0181] Continue stirring for 20 minutes, then cool to room temperature to obtain a stable small-particle-size ammonia-terminated polysiloxane emulsion.
[0182] Example 2
[0183] This embodiment is basically the same as Example 1, except that the amount of dodecyl alcohol polyether-12 is 9.0 g and the amount of isomeric tridecyl alcohol polyoxyethylene ether-12 is 10.0 g, with a mass ratio of 0.90:1. Any shortfall is made up with deionized water. The mass ratio of hexadecyltrimethylammonium chloride in the first and second cationic emulsions is 45:55. The stirring speed before phase inversion is 850 rpm. The pH of the resulting emulsion is adjusted to 7.7 ± 0.1.
[0184] Example 3
[0185] This embodiment is basically the same as that in Embodiment 1, except that the dodecyl alcohol polyether-12 is 10.0 g and the isomeric tridecyl alcohol polyoxyethylene ether-12 is 9.0 g, with a mass ratio of 1.11:1. The insufficient mass is made up by deionized water.
[0186] The mass ratio of hexadecyltrimethylammonium chloride in the first cationic emulsion to the second cationic emulsion is 55:45. The stirring speed during the phase inversion stage is 950 rpm. The final pH of the emulsion is 7.9 ± 0.1.
[0187] Example 4
[0188] This embodiment is basically the same as Example 1, except that: the mass ratio of hexadecyltrimethylammonium chloride contained in the first cationic emulsion and the second cationic emulsion is 40:60; the mass ratio of dodecyl alcohol polyether-12 to isomeric tridecyl alcohol polyoxyethylene ether-12 is still 1:1; and the final pH of the emulsion is 7.6±0.1.
[0189] Comparative Example 1
[0190] Compared to Example 1, only dodecyl alcohol polyether-12 was omitted, while the other steps remained unchanged. The amount of isomeric tridecyl alcohol polyoxyethylene ether-12 was maintained at 10.0 g.
[0191] Comparative Example 2
[0192] Compared to Example 1, only isomeric tridecyl alcohol polyoxyethylene ether-12 was omitted. The amount of dodecyl alcohol polyether-12 remained at 10.0 g.
[0193] Comparative Example 3
[0194] The formulation is exactly the same as in Example 1, except that dodecyl alcohol polyether-12 and isotridecyl alcohol polyoxyethylene ether-12 are premixed and then added to the amino-containing polysiloxane in one step. The sequential pretreatment of dodecyl alcohol polyether-12 followed by isotridecyl alcohol polyoxyethylene ether-12 is not performed.
[0195] Comparative Example 4
[0196] The formulation is the same as in Example 1, but dodecyl alcohol polyether-12, isotridecyl alcohol polyoxyethylene ether-12, and hexadecyltrimethylammonium chloride are all added to the aqueous phase beforehand, and then the aqueous phase containing emulsifier is added to the ammonia-terminated polysiloxane oil phase. No pre-interfacialization of the oil phase is performed.
[0197] Comparative Example 5
[0198] Compared with Example 1, the pre-interfacial treatment of the nonionic emulsifier remained unchanged, but the hexadecyltrimethylammonium chloride was not divided into first and second parts, but was added all at once with the aqueous phase before phase inversion.
[0199] Comparative Example 6
[0200] The formulation and emulsifier addition order are the same as in Example 1, but the slow water addition process in the critical phase inversion region is eliminated, and the first aqueous phase is added quickly in one go in a short time.
[0201] Comparative Example 7
[0202] Cyclic siloxanes and amino-functionalized siloxanes were fully polymerized to obtain an amino-terminated polysiloxane base oil with significantly improved viscosity. After cooling and storage, the oil was reheated to 55°C and emulsified according to the emulsifier formulation of Example 1.
[0203] Comparative Example 8
[0204] The total amount of dodecyl alcohol polyether-12 and isotridecyl alcohol polyoxyethylene ether-12 added remained unchanged, and their mass ratio was adjusted to 0.40:1. The remaining conditions were the same as in Example 1.
[0205] Comparative Example 9
[0206] The mass ratio of dodecyl alcohol polyether-12 to isotridecyl alcohol polyoxyethylene ether-12 was adjusted to 2.0:1, while the total emulsifying dosage remained unchanged.
[0207] Comparative Example 10
[0208] The emulsion was prepared according to the method in Example 1, but the pH of the emulsion was finally adjusted to 5.8 ± 0.1 using glacial acetic acid.
[0209] Comparative Example 11
[0210] The emulsion was prepared according to the method of Example 1, but the final pH was adjusted to 9.5 ± 0.1.
[0211] The measured Zeta potential was +12.4 mV, the initial particle size was 52.6 nm, and the PDI was 0.229. Significant flocculation and particle size increase occurred during storage.
[0212] Comparative Example 12
[0213] Instead of implementing the critical phase inversion low-speed interface formation process in Example 1, conventional rapid pre-emulsification was used, followed by high-intensity homogenization to mechanically break down the droplets into smaller particle sizes. By increasing the homogenization intensity, the initial particle size reached approximately 39.6 nm, close to that of the embodiment of the present invention. However, its PDI was 0.207, and the particle size increased significantly during storage at 45°C.
[0214] III. Performance Testing Methods
[0215] 1. Particle size and PDI testing
[0216] The Z-mean particle size and PDI of the samples were determined using a dynamic light scattering nanoparticle size analyzer. 0.10 g of the emulsion to be tested was diluted with deionized water to a suitable scattering intensity and gently mixed, avoiding the introduction of large amounts of air bubbles. The test temperature was 25 ± 0.2℃; the sample equilibration time was 120 s; each sample was tested three times consecutively; the average of the three measurements was taken as the final result. A lower PDI indicates a more concentrated droplet size distribution.
[0217] 2. Zeta potential test
[0218] The determination was performed using a nanoparticle size and Zeta potential analyzer. The emulsion was diluted with deionized water to a suitable concentration, equilibrated at 25°C for 120 s, and then tested. Each sample was tested in triplicate.
[0219] 3. Accelerated stability at 45℃
[0220] Take 50 g of each emulsion sample and place it in a sealed transparent sample bottle. Store it in a constant temperature environment of 45±1℃ for 90 days. Take samples at 0, 30, 60 and 90 days to detect Z-mean particle size and PDI, and observe: whether there is oil floating; whether there is stratification; whether there is visible flocculation; whether there is precipitation; and whether there is obvious color change.
[0221] The particle size growth rate is calculated using the following formula: Particle size growth rate (%) = (90-day particle size - initial particle size) / initial particle size × 100%.
[0222] 4. Low-temperature stability
[0223] Each emulsion was stored at 0±1℃ for 90 days. The appearance of the emulsions was observed at 30 days, 60 days, and 90 days. After 90 days, the temperature was restored to 25℃ for 24 hours, and the particle size and PDI were tested again.
[0224] 5. Centrifugal stability
[0225] Add 10 mL of sample to a centrifuge tube and centrifuge at 4000 rpm for 30 min at 25℃. After centrifugation, observe whether the following occurs: oil-water separation; floating oil layer; obvious flocculation; or bottom sedimentation.
[0226] 6. Freeze-thaw cycle stability
[0227] The samples were kept at -10°C for 24 h, then transferred to 25°C and kept there for another 24 h, constituting one freeze-thaw cycle. Five cycles were performed consecutively. After the fifth cycle, the appearance of the samples was observed, and the particle size and PDI were measured.
[0228] IV. Results of Basic Emulsion Properties
[0229]
[0230] High and low temperature and freeze-thaw stability results
[0231]
[0232] Shampoo compound stability test
[0233] Tests were conducted using a standardized transparent shampoo base. The amount of ammonia-terminated polysiloxane emulsion added to the shampoo was uniformly 1.0 wt%. The shampoo base included sodium lauryl ether sulfate, sodium lauroyl sarcosinate, cocamidopropyl betaine, and commonly used conditioning, thickening, and preservative components. Each emulsion was added to the same shampoo base. After standing at 25°C for 24 hours, the appearance and viscosity were tested, followed by storage at 45°C for 30 days to test system changes. Shampoo without ammonia-terminated polysiloxane emulsion was used as a blank control.
[0234] Viscosity retention rate is calculated using the following formula:
[0235] Viscosity retention rate (%) = Shampoo viscosity after storage at 45℃ / Shampoo viscosity before storage × 100%.
[0236] Shampoo compound stability results
[0237]
[0238] Hair conditioning performance test
[0239] 1. Hair strand pretreatment
[0240] Damaged hair bundles of the same batch, length, and quality were selected. Each bundle weighed 10.0 ± 0.2 g and was 20 cm long. The hair bundles were immersed in a 1 wt% sodium dodecyl sulfate aqueous solution for 30 min. They were then rinsed thoroughly with running water. The bundles were then equilibrated for 24 h at a temperature of 22 ± 2℃ and a relative humidity of 50 ± 5%.
[0241] 2. Wet combing performance test
[0242] Take a treated hair strand and wash it with the same amount of test shampoo in a standardized manner. Keep the hair wet after rinsing.
[0243] Using a texture analyzer or combing force tester, a standard comb is passed through the hair bundle at the same speed, and the integral area of the force-displacement curve during one complete combing process is recorded; the combing work is used to represent the wet combing resistance, and the lower the value, the better the wet combing performance.
[0244] 3. Dry combing performance test
[0245] After the hair strands were allowed to dry naturally and equilibrated under constant temperature and humidity conditions for 24 hours, the dry combing performance was measured using the same method.
[0246] 4. Smooth and soft feel when wet.
[0247] Five trained evaluators scored the participants using a 10-point scale.
[0248] A score of 1 indicates significant sluggishness during the wet brewing process;
[0249] A score of 10 indicates that the wet rinsing process is very smooth.
[0250] Each hair strand was evaluated three times, and the average value was calculated.
[0251] 5. Smooth and silky feel after drying
[0252] The hair strands were touched and combed for evaluation within 15 minutes after drying.
[0253] A 10-point scale is used.
[0254] 6. Antistatic properties
[0255] The dried hair strands were equilibrated for 24 hours in an environment with a temperature of 22±2℃ and a relative humidity of 40±5%.
[0256] Five measurements were taken at different locations on the hair strand using a surface resistance meter, and the average value was recorded.
[0257] The angle of hair scattering or the area of hair scattering after standard combing can also be added as an auxiliary evaluation indicator.
[0258] Hair performance results
[0259] Blank Shampoo 286 241 4.1 4.3 Example 1 112 91 9.2 9.1 Example 2 121 98 8.9 8.8 Example 3 125 102 8.8 8.7 Example 4 132 109 8.6 8.5 Comparative Example 1 174 145 7.2 7.1 Comparative Example 2 165 137 7.5 7.4 Comparative Example 3 148 123 8.0 7.9 Comparative Example 4 193 161 6.7 6.6 Comparative Example 5 155 129 7.8 7.7 Comparative Example 6 202 169 6.4 6.2 Comparative Example 7 216 181 6.0 5.9 Comparative Example 8 171 142 7.3 7.2 Comparative Example 9 168 140 7.4 7.3 Comparative Example 10 160 133 7.6 7.5 Comparative Example 11 187 156 6.8 6.7 Comparative Example 12 151 127 7.9 7.6
[0260] Antistatic performance results
[0261] Test the surface resistance of the hair strand after treatment.
[0262]
[0263] As can be seen from Examples 1-4 and Comparative Examples 1-2, dodecyl alcohol polyether-12 and isomeric tridecyl alcohol polyoxyethylene ether-12 cannot be arbitrarily substituted for each other.
[0264] When only one of the nonionic emulsifiers is used, the initial particle size increases from 31.7 nm in Example 1 to 72.6 nm and 61.8 nm, respectively, and the PDI also increases significantly, indicating that there is a significant synergistic effect between the two nonionic emulsifiers with different structures.
[0265] Among them, dodecyl alcohol polyether-12 is more conducive to reducing the interfacial energy required to form a new oil-water interface, while isomeric tridecyl alcohol polyoxyethylene ether-12, due to the branched structure of the hydrophobic group, can generate more obvious steric hindrance during the droplet approach process.
[0266] When both exist simultaneously, they can take into account both the formation of a new interface and the anti-agglomeration performance between droplets after formation.
[0267] Further comparison of Example 1 and Comparative Example 3 shows that, under the condition that the types and total amounts of the two nonionic emulsifiers are exactly the same, simply changing the order of addition can further reduce the particle size from 48.9 nm to 31.7 nm and the PDI from 0.198 to 0.125.
[0268] This indicates that the sequential addition defined in this invention is not a simple change in process, but rather affects the initial distribution of the emulsifier in the oil phase and its arrangement when it subsequently enters the new interface.
[0269] The difference between Example 1 and Comparative Example 4 is more significant.
[0270] When all three emulsifiers were pre-placed in the aqueous phase, the initial particle size of the emulsion increased to 83.7 nm, and the PDI reached 0.317.
[0271] This indicates that whether the emulsifier is pre-contaminated with amino-containing polysiloxanes significantly affects droplet formation.
[0272] Comparing Example 1 and Comparative Example 5, it can be seen that even if the total amount of cationic emulsifier is exactly the same, adding it once will increase the particle size to 54.2 nm.
[0273] Of particular note is that the Zeta potential of Comparative Example 5 was +26.8 mV, which was even slightly higher than the +25.34 mV of Example 1, but its emulsion stability was significantly worse.
[0274] Therefore, the stabilizing effect of this invention cannot be simply attributed to "increasing the zeta potential".
[0275] The key is the matching between the timing of the cationic emulsifier entering the interface and the interface formation process.
[0276] Example 1 and Comparative Example 6 further demonstrate the importance of the critical phase transition stage.
[0277] After the controlled water addition in the critical region was removed, the initial particle size rapidly increased to 96.5 nm, and the PDI reached 0.348.
[0278] This indicates that when too many new interfaces are generated in a short period of time during the phase transition critical stage, the emulsifier cannot cover all interfaces in time, thus causing the new droplets to collide and re-aggregate rapidly.
[0279] The comparison between Example 1 and Comparative Example 7 illustrates that the degree of polymerization is not a typical reaction parameter independent of the emulsification process.
[0280] Polysiloxane was fully polymerized into a high-viscosity base oil and then emulsified using the same emulsifier, resulting in an initial particle size of 142.8 nm.
[0281] This demonstrates that the pre-emulsification polymerization window employed in this invention reduces the interfacial deformation energy required for the formation of high-viscosity polysiloxane droplets.
[0282] The comparison between Example 1 and Comparative Examples 8-9 further demonstrates that there is a preferred ratio window between the two nonionic emulsifiers.
[0283] When the mass ratio of dodecyl alcohol polyether-12 to isotridecyl alcohol polyoxyethylene ether-12 deviates from the preferred range, the emulsion particle size and PDI still increase significantly even when both emulsifiers are present.
[0284] This shows that achieving optimal technical results does not depend solely on whether or not an emulsifier is present, but is further influenced by the relative proportion of the two.
[0285] Comparative Examples 10 and 11 demonstrate that the stability of the emulsion is also affected by the final pH.
[0286] When the pH is too low, the Zeta potential increases significantly, but the storage stability does not increase accordingly; when the pH is too high, the Zeta potential decreases, the electrostatic repulsion between droplets is insufficient, and obvious aggregation occurs during storage.
[0287] Therefore, the pH window defined in this invention is not simply to meet the requirements for use in washing and care products, but is related to the stability of amino-containing polysiloxanes and the cationic interface.
[0288] Of particular note is comparison 12.
[0289] By improving the mechanical homogeneity, the initial particle size of Comparative Example 12 can reach 39.6 nm, which is quite close to that of Example 1.
[0290] However, after being stored at 45°C for 90 days, the particle size increased to 61.8 nm, with a particle size growth rate of 56.1%, while the particle size growth rate of Example 1 was only 7.6%.
[0291] This shows that traditional methods can obtain "temporarily small particle size" by increasing mechanical energy, but cannot obtain the same long-term interface stability as the present invention.
[0292] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a stable small-particle-size ammonia-terminated polysiloxane emulsion, characterized in that, Includes the following steps: (1) Cyclic siloxane D4 and amino functional siloxane monomers are subjected to ring-opening polymerization in the presence of an alkaline catalyst so that the resulting amino-containing polysiloxane reaches the predetermined pre-emulsification polymerization state. (2) Adjust the amino-containing polysiloxane obtained in step (1) to 50-60°C, first add dodecyl alcohol polyether-12 for the first pre-interfacial treatment, then add isomeric tridecyl alcohol polyoxyethylene ether-12 for the second pre-interfacial treatment to obtain the pre-interfacialized oil phase. (3) Separate the aqueous solution of hexadecyltrimethylammonium chloride into a first cationic aqueous phase and a second cationic aqueous phase; (4) Under the conditions of 50-60℃ and stirring, the first cationic aqueous phase is added to the pre-interfacialized oil phase obtained in step (2). When the system enters the phase inversion critical region, the rate of addition of the aqueous phase is controlled so that the system is transformed from the oil continuous phase to the water continuous phase. (5) After the phase inversion is complete, add the second cation aqueous phase and the remaining deionized water; (6) The pH of the obtained emulsion is adjusted to 7.5-8.0 using an acidic regulator to obtain the stable small particle size ammonia-terminated polysiloxane emulsion; The cyclic siloxane D4 comprises 20-30%, and the amino-functionalized siloxane monomer comprises 0.5-1.5%. The dodecyl alcohol polyether-12 is 3-5%, and the isomeric tridecyl alcohol polyoxyethylene ether-12 is 3-5%; The mass ratio of dodecyl alcohol polyether-12 to isotridecyl alcohol polyoxyethylene ether-12 is 0.75 to 1.30:
1.
2. The preparation method according to claim 1, characterized in that, The ring-opening polymerization temperature in step (1) is 100-110℃.
3. The preparation method according to claim 1, characterized in that, The first cationic aqueous phase contains 30-70% of the total amount of hexadecyltrimethylammonium chloride, and the second cationic aqueous phase contains the remainder of hexadecyltrimethylammonium chloride. The mass ratio of hexadecyltrimethylammonium chloride in the first cationic aqueous phase and the second cationic aqueous phase is 40–60:60–40.
4. The preparation method according to claim 1, characterized in that, In step (4), the rate of water phase addition in the reverse inversion critical region is lower than the rate of water phase addition after the reverse inversion is completed.
5. The preparation method according to claim 1, characterized in that, The stirring speed in step (4) is 800-1000 rpm.
6. The preparation method according to claim 1, characterized in that, The zeta potential of the emulsion obtained in step (6) is +20 to +35 mV.
7. A stable small-particle-size ammonia-terminated polysiloxane emulsion, characterized in that, The emulsion is prepared by the method according to any one of claims 1 to 6, wherein the Z-average particle size is 20 to 50 nm and the PDI is not greater than 0.
20.
8. The ammonia-terminated polysiloxane emulsion according to claim 7, characterized in that, The Z-average particle size is 25–40 nm, and the PDI is not greater than 0.
15.
9. A hair shampoo and conditioner composition, characterized in that, Includes the ammonia-terminated polysiloxane emulsion as described in claim 6 or 7, as well as anionic surfactants and / or amphoteric surfactants.
10. The use of the amino-terminated polysiloxane emulsion of claim 7 in shampoos, conditioners, hair masks or scalp care products.